Quercetin positively affects gene expression profiles and metabolic pathway of antibiotic-treated mouse gut microbiota - Mi, Wei; Hu, Zhiyong; Xu, Lanlan; Bian, Xiangyu; Lian, Wu; Yin, Shuying; Zhao, Shuying; Gao, Weina; Guo, Changjiang; Shi, Tala (Frontiers in Microbiology, 2022)
Quercetin has a wide range of biological properties that can be used to prevent or decrease some diseases. In this study, we aimed to investigate the gene expression profile and metabolic pathway of the gut microbiota of an antibiotic-treated mouse model administered quercetin. Blood, feces, and intestinal tissue samples were collected and metagenomic sequencing, enzyme-linked immunosorbent assay, and western blot analysis were used to detect variations. The result showed that compared with the model group, the quercetin-treated group exhibited increased levels of health beneficial bacterial species, including Faecalibaculum rodentium (103.13%), Enterorhabdus caecimuris (4.13%), Eggerthella lenta (4%), Roseburia hominis (1.33%), and Enterorhabdus mucosicola (1.79%). These bacterial species were positively related to butyrate, propionate, and intestinal tight junction proteins (zonula occludens [ZO]-1 and occludin) expression, but negatively related to serum lipopolysaccharide (LPS) and tumor necrosis factor (TNF)-α levels. In addition, the metabolic pathway analysis showed that dietary quercetin significantly enhanced spliceosomes (111.11%), tight junctions (62.96%), the citrate cycle (10.41%), pyruvate metabolism (6.95%), and lysine biosynthesis (5.06%), but decreasing fatty acid biosynthesis (23.91%) and N-glycan (7.37%) biosynthesis. Furthermore, these metabolic pathway changes were related to relative changes in the abundance of 10 Kyoto Encyclopedia of Genes and Genomes (KEGG) genes (K00244, K00341, K02946, K03737, K01885, k10352, k11717, k10532, K02078, K01191). In conclusion, dietary quercetin increased butyrate-producing bacterial species, and the acetyl-CoA-mediated increased butyrate accelerated carbohydrate, energy metabolism, reduced cell motility and endotoxemia, and increased the gut barrier function, thereby leading to healthy colonic conditions for the host.